Correlation between the Expression of E6 HPV with p53 and p16INK4A at Cervical Adenocarcinoma and Cervical Normal - Gondo Mastutik1 , Alphania Rahniayu2,3, Nila Kurniasari2,3, Anny Setijo Rahaju2,3, Rahmi Alia4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Cervical adenocarcinoma is the second most common type of cervical cancer. The markerto predict the risk of this cancer is still need to be improved. This study aimed to evaluate the correlationbetween expression of E6 HPV with p53 and p16INK4A in cervical adenocarcinoma and cervical normal.Methods: This study was a cross sectional study conducted at the Department of Anatomic Pathology, Dr.Soetomo General Academic Hospital Surabaya Indonesia using 49 paraffin blocks during period JanuaryDecember 2017. The E6 HPV, p53, and p16INK4A expression were detected by immunohistochemistrystaining. Results: There were significant differences between the expression of E6 HPV and p16INK4Ain cervical adenocarcinoma and cervical normal, but the expression of p53 was no significant differencewith p=0.060 (P>0.05). There was a positive correlation between the expression of E6 HPV with p53 andp16INK4A (p<0.05) in cervical adenocarcinoma and cervical normal, and in cervical adenocarcinoma group,there was a significant correlation between the expression of E6 HPV with p53 (p=0.004) and p16INK4A(p=0.028), but no correlation was found between p53 with p16INK4A expression (p=0,092). Conclusion:It suggests that p16INK4A might serve as marker for predicting the risk of developing cervical cancer fromthe epithelium of cervical normal.